2020
DOI: 10.48084/etasr.3248
|View full text |Cite
|
Sign up to set email alerts
|

Improved Steel Beam-Column Connections in Industrial Structures

Abstract: Beam-to-column connection is a rigid connection used in steel moment frames which acts as the main resisting system in structural design. Haunches with double beam section height at the eave, ridge and crane bracket are usually used to resist the large bending moment at the critical locations of the steel frames. Damper devices can be used as the main source of producing forces used to reduce the bending moment due to different static and dynamic loads. This study focuses on improving the steel beam-column con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…So for the gusset plate stiffness the calculation was. (11) The composite action between concrete and steel had an impact on connection stiffness. There is an additional stiffness from the reinforcement with the following Equation below.…”
Section: Figure 6 Study Flowchartmentioning
confidence: 99%
See 1 more Smart Citation
“…So for the gusset plate stiffness the calculation was. (11) The composite action between concrete and steel had an impact on connection stiffness. There is an additional stiffness from the reinforcement with the following Equation below.…”
Section: Figure 6 Study Flowchartmentioning
confidence: 99%
“…All of the studies used the bolted connection and a slip-in gusset plate. Other non-composite connections discussed a portal frame [16−19], improvised connection for industrial structure [11], and welded connection in HRS beam-column [20].…”
mentioning
confidence: 99%
“…Full-depth stiffeners in the beam flanges avoid local buckling of the beam flange and allow to occur outside the haunch length. In addition, experimental and analytical studies have shown that a T-shaped haunch with triangular geometry is the most effective type of haunches among the different shapes [23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen and Kim developed a plastic hinge method using stability functions for nonlinear dynamic analysis of steel frames [6,7,13], including the effects of semi-rigid connections and also developed distributed plasticity methods using stability functions for nonlinear dynamic analysis of semi-rigid steel frames employed by the Hilber-Hughes-Taylor method for solving dynamic equations [14,15,17]. Recently, authors in [26][27][28] tried to investigate the behavior of steel frames with the effects of connections. To the best of our knowledge, there is no study on the fiber plastic hinge method using stability functions for nonlinear dynamic analysis of steel frames.…”
Section: Introductionmentioning
confidence: 99%